Design of Three-factor Response Surface Optimization of Camouflaged Capecitabine Nanoerythrovesicles - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2016)
systems. By taking cues for designing long circulating carriers from natural entities such as red blood cells (RBCs) have been explored for many years. Among all the cellular carriers including leukocytes, fibroblast, islets, and hepatocytes, RBCs offer several distinctive features. Nanovesicles (NVs) represent a novel transporter for cell signals to modify functions of target cell. Therefore, NVs play many roles in both physiological and pathological process. Materials and Methods: This report highlights biogenesis, composition, and biological rules of erythrocytes-derived NVs (EDNVs). Furthermore, we address utilization of EDNVs as novel drug delivery cargo as well as therapeutic target. EDNVs are biocompatible, biodegradable, efficient drug loading target specificity, and prolonged biological half-life. It is also rich in phospholipids, proteins, lipid raft, and hemoglobin. Results and Discussion: In this study, nanosize lipoprotein membrane vesicles (EDNVs) bearing capecitabine were prepared by sonication method. An optimized EDNV was obtained through implementation of Box-Behnken experimental design. Developed capecitabine nanoerythrosomes conjugate formulation were preliminary optimized on the basis of vesicle morphology, size and size distribution, loaded drug concentration, and in vitro release studies. Conclusion: Targeting efficiency of drug-loaded erythrocytes over free drug is higher, which may provide increased therapeutic index and drug targeting to various organs. It may help in the reduction of dose required for the therapy and there by dose-related systemic side effects could also be minimized.